Are firm size, firm complexity, and managerial ownership able to affect audit fee?: The evidence in Philippines and Indonesia as emerging countries - Bayu Hartarto Syafii; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2022)
There are some factors that are influential in increasing the audit fee. This study aims to determine several factors affecting the increasing audit fees. Several factors that can affect the increasing audit fees for companies are firm size, firm complexity, and managerial ownership, with return on assets and leverage for controlling factors. This research is a quantitative method that uses all data collected as a sample. The main data are financial statements of Indonesian companies listed on the Indonesia stock exchange, and financial statements of Philippine companies listed on the Philippines stock exchange in 2017-2019 with the total sample of each country is 82 companies and 36 companies. Analyze were performed the classical assumption test, multiple linear regression analysis using SPSS 23 version. The results of the study show that firm size and firm complexity significantly influence audit fees. in contrast, managerial ownership has no significant effect on audit fees.